Galactic cosmic ray simulation at the NASA space radiation laboratory – Progress, challenges and recommendations on mixed-field effects. (February 2023) - Huff, Janice L.; Poignant, Floriane; Rahmanian, Shirin; Khan, Nafisah; Blakely, Eleanor A.; Britten, Richard A.; Chang, Polly; Fornace, Albert J.; Hada, Megumi; Kronenberg, Amy; Norman, Ryan B.; Patel, Zarana S.; et al.
Highlights: A virtual workshop on galactic cosmic ray simulation at the NASA Space Radiation Lab was held in 2020. The GCR simulator (GCRsim) represents the radiation field encountered by humans in deep space behind shielding. Automated delivery of the 33-ion sequential GCR simulator field takes approximately 75 minutes. The GCR simulator and delivery approach are considered scientifically sound and state of the art. Abstract: For missions beyond low Earth orbit to the moon or Mars, space explorers will encounter a complex radiation field composed of various ion species with a broad range of energies. Such missions pose significant radiation protection challenges that need to be solved in order to minimize exposures and associated health risks. An innovative galactic cosmic ray simulator (GCRsim) was recently developed at the NASA Space Radiation Laboratory (NSRL) at Brookhaven National Laboratory (BNL). The GCRsim technology is intended to represent major components of the space radiation environment in a ground analog laboratory setting where it can be used to improve understanding of biological risks and serve as a testbed for countermeasure development and validation. The current GCRsim consists of 33 energetic ion beams that collectively simulate the primary and secondary GCR field encountered by humans in space over the broad range of particle types, energies, and linear energy transfer (LET) of interest to health effects. A virtual workshop was held in December 2020 to assess the status of the NASA baseline GCRsim. Workshop attendees examined various aspects of simulator design, with a particular emphasis on beam selection strategies. Experimental results, modeling approaches, areas of consensus, and questions of concern were also discussed in detail. This report includes a summary of the GCRsim workshop and a description of the current status of the GCRsim. This information is important for future advancements and applications in space radiobiology.